Pengaruh Relasi Melayu Nusantara Dalam Mempererat Integrasi Sosial Menuju Pembentukan Negara Bangsa - Touwe, Sem; Far-Far, Gazali (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pattimura, 2021)
Since ancient times, the Malays have been known as a maritime community, predominantly inhabiting the western part of the Archipelago. Unbeknownst to many, they have played an active role in fostering social relations and building solidarity, contributing to forming a unified nation-state, with the Malay language serving as a vital symbol of this unity. This paper explores the role of the Malay language and Malay relations in building solidarity among the peoples of the Archipelago. To address these questions, the paper aims to (1) Explain the role of the Malay language as a cultural symbol that unites various tribes and nations within the Archipelago, (2) Discuss how Malay history and culture have strengthened national integration, and (3) Examine the consensus that legitimized Indonesian as the language of unity. The data and information in this paper are derived from a literature review of various research reports, book reviews, and documents to describe relevant theories and information from the past and present. These resources are then organized for analysis. The study results indicate that the relations among Malays in the Archipelago, particularly in trade and culture, have effectively built solidarity among tribes, ethnicities, and groups. This solidarity, primarily facilitated through the symbol of the Malay language, has had positive implications for forming a nation-state.